Categorification and higher representation theory - Beliakova, Anna; Lauda, Aaron D. (Providence : American Mathematical Society, 2017)
Presents some of the current trends in higher representation theory and the diverse techniques that are being employed in this field with the aim of showcasing the many applications of higher representation theory. The companion volume (Contemporary Mathematics, Volume 684) is devoted to categorification in geometry, topology, and physics.
I. Losev, Rational Cherednik algebras and categorificationO. Dudas, M. Varagnolo, and E. Vasserot, Categorical actions on unipotent representations of finite classical groupsJ. Brundan and N. Davidson, Categorical actions and crystals A. M. Licata, On the 2-linearity of the free group M. Ehrig, C. Stroppel, and D. Tubbenhauer, The Blanchet-Khovanov algebras G. Lusztig, Generic character sheaves on groups over $k[\epsilon]/(\epsilon^r)$ D. Berdeja Suarez, Integral presentations of quantum lattice Heisenberg algebras Y. Qi and J. Sussan, Categorification at prime roots of unity and hopfological finiteness B. Elias, Folding with Soergel bimodules L. T. Jensen and G. Williamson, The $p$-canonical basis for Hecke algebras.
Includes bibliographical references.
Keywords: Categories (Mathematics); Mathematical analysis; Algebra